RESPIRATORY ADENOVIRUS INFECTIONS IN IRAQ (2020–2025): EPIDEMIOLOGICAL AND MOLECULAR OVERVIEW - Obeed, Ameer Najy; Wetwet, Nadhema Bahaa; Kareem, Baneen Maan (PT. Antis International Publisher, 2026)
Objective: This study provides an updated assessment of respiratory adenovirus infections in Iraq from 2020 to 2025 by examining national trends in incidence, demographic distribution, and circulating viral strains. Method: Data were collected from multiple medical centers and health institutions across Iraq, and patient samples were analyzed using molecular diagnostic techniques, including PCR-based detection and genotyping, to identify prevalent adenovirus types. Epidemiological indicators were evaluated to determine infection patterns among different age groups. Results: The findings reveal a gradual increase in reported respiratory adenovirus cases over the study period, with the highest incidence occurring among young children and older adults. Molecular analysis identified human adenovirus types 3, 7, and 14 as the most frequently detected variants, reflecting their continued circulation and clinical relevance. Novelty: This research provides one of the most recent national overviews of adenovirus activity in Iraq, integrating multicenter epidemiological data with molecular characterization to highlight emerging trends and strain distribution, underscoring the need for strengthened surveillance and expanded diagnostic capacity.